(untitled) - London, Manuel (San Francisco, 2007)
The authors bring each of their unique perspectives and backgrounds to create a comprehensive guide to leading small groups. Recommended reading for both the novice and experienced group leader
Keywords: Small groups,Leadership,Nghệ thuật lãnh đạo